Research of Conversion Processes of Renewable Origin Electric Power - Ramonas, Č.; Kepalas, V.; Adomavičius, V. (Elektronika ir Elektrotechnika, 2006)
Supply of electric power, which is converted from renewable energy sources (solar, wind, hydro) into the electric grid of standard parameters through the grid-synchronized inverter is being analysed in this paper. The researched scheme has an intermediate chain of LC type for short duration energy accumulation. The equivalent scheme of the system was worked out and presented in this paper as well as its mathematical description. The mathematical model of the power conversion system was elaborated for the package of programs MATLAB/SIMULINK on basis of equations of power conversion processes. Results of simulation show that power conversion system with the intermediate chain for energy accumulation and pulse-width modulation allows achieving of electric current shape, which can meet the requirements for supplying into electric grid. Ill. 8, bibl. 9 (in Lithuanian, summaries in English, Russian and Lithuanian).